The management of endoscopic retrograde cholangiopancreatography-related infections risk: results of an italian survey at regional level - Cennamo, V.; Landi, S.; Aragona, G.; Colecchia, A.; Conigliaro, R.; Di Lorenzo, D.; Di Marco, M.; Fabbri, C.; Falcone, P.; Gaiani, F.; Manno, M.; Merighi, A.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background and aim. Among the Endoscopic retrograde cholangiopancreatography (ERCP) adverse events, an increasingly arising problem is the transmission of Multi Drug Resistant (MDR) Bacteria through duodenoscopes. The aim of this survey was to evaluate the current clinical practice of management of ERCP associated infections in Emilia-Romagna, Italy.Methods. An online survey was developed including 12 questions on management of ERCP associated infections risk. The survey was proposed to all 12 endoscopy centers in Emilia Romagna that perform at least > 200 ERCPs per year. Results. 11 centers completed the survey (92%). Among all risk factors of ERCP infections, hospitalization in intensive care units, immunosuppressant therapies, and previous MDR infections have achieved a 80 % minimum of concurrence by our respondents. The majority of them did not have a formalized document in their hospital describing categories and risk factors helpful in the detection of patients undergoing ERCP with an high-level infective risk (9/11, 82%).Most centers (8/11, 72%) do not perform screening in patients at risk of ERCP infections. Post procedural monitoring is performed by 6 of 11 centers (55%).Conclusion. Our survey showed that, at least at regional level, there is a lack of procedures and protocols related to the management of patients at risk of ERCP infections.